2002
DOI: 10.1118/1.1448824
|View full text |Cite
|
Sign up to set email alerts
|

Effect of respiratory gating on reducing lung motion artifacts in PET imaging of lung cancer

Abstract: Positron emission tomography (PET) has shown an increase in both sensitivity and specificity over computed tomography (CT) in lung cancer. However, motion artifacts in the 18F fluorodioxydoglucose (FDG) PET images caused by respiration persists to be an important factor in degrading PET image quality and quantification. Motion artifacts lead to two major effects: First, it affects the accuracy of quantitation, producing a reduction of the measured standard uptake value (SUV). Second, the apparent lesion volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
402
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(421 citation statements)
references
References 13 publications
7
402
1
5
Order By: Relevance
“…This study showed that quantification of volumetric parameters of 4D PET/CT images using an adaptive contrastoriented thresholding algorithm and 3D lesion-based partial volume correction is feasible, and we observed only a slight increase in the quantification of metabolic activity of lung malignancies using the highest respiratory-gated versus nongated PET/CT images which is in contrast to previous respiratory-gated PET/CT studies [14,33]. Partial volume correction increased both the respiratory-gated and nongated values significantly and appears to be the dominant source of quantitative error of lung malignancies.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…This study showed that quantification of volumetric parameters of 4D PET/CT images using an adaptive contrastoriented thresholding algorithm and 3D lesion-based partial volume correction is feasible, and we observed only a slight increase in the quantification of metabolic activity of lung malignancies using the highest respiratory-gated versus nongated PET/CT images which is in contrast to previous respiratory-gated PET/CT studies [14,33]. Partial volume correction increased both the respiratory-gated and nongated values significantly and appears to be the dominant source of quantitative error of lung malignancies.…”
Section: Discussioncontrasting
confidence: 68%
“…In phasebased respiratory gating, the respiratory cycle is divided into separate phase ranges, while amplitude gating divides the respiratory amplitude into different amplitude ranges [13]. In 2002, Nehmeh et al were the first to perform respiratory gating for PET scanning in clinical setting and found that respiratory gating decreases total lesion volume and increases measured SUV compared to non-gated images [14]. Gating has also been reported to improve the diagnosis of malignant lung lesions and the evaluation of response to radiation treatment [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…[66][67][68][69][70][71][72][73][74][75] One approach to improve registration between the CT and the PET data is to bring the temporal resolution of the CT images to that of the PET data. 42 Recognizing the fact that PET is averaged over many breath cycles, a CT image averaged over 1 breath cycle should improve registration between the CT and the PET data.…”
Section: Average Ct Of Less Than 1 Msv Reduces Misregistrationmentioning
confidence: 99%
“…84 It was adopted for tumor imaging of the thorax almost a decade ago, 60,[66][67][68] about the same time when 4-dimensional CT was launched. 62,[77][78][79]85 Today, 4-dimensional CT has been accepted as a standard practice in CT imaging of tumor motion for radiation therapy.…”
Section: -Dimensional Pet Imagingmentioning
confidence: 99%
“…This could result in significant underdosing of target volumes and increased doses to healthy tissues, particularly for highly conformal techniques applied to thoracic and abdominal malignancy treatments 1 , 2 , 3 . Attempts to contend with organ deformation in image‐guided and adaptive radiotherapy often involve the implementation of deformable image registration (DIR) algorithms 4 , 5 , 6 , 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%